Comparison Of Visual Acuity And Contrast Sensitivity Between Unilateral Primary Pterygium And Normal Adults Utilizing Computerized M&S Smart System Ii - Hilmi, Mohd Radzi; Norazmar, Nur Ain; Mohd Kamal, Khairidzan; Che Azemin, Mohd Zulfaezal; Maruziki, Nur Nabilah; Musa, Nur Hidayah; Nasir, Mardhiah Syazwani (International Islamic University Malaysia (IIUM), 2019)
Introduction: This paper aimed to describe variation in oculovisual function between unilateral primary pterygium and normal adults using computerized M&S Smart System II. Methods: A total of 120 participants comprise 60 unilateral primary pterygium eyes from 60 pterygium patients and 60 normal adults were recruited in this study. Diagnosis and classification of primary pterygium were done by a consultant ophthalmologist (KMK). Standard optometric examinations were performed in all participants. Oculovisual function parameters were taken based on the best-corrected visual acuity (BCVA) and contrast sensitivity (CS) which was subjectively measured using computerized M&S Technologies Smart System II. Both measurements were done by single operator and performed on the same visit. Difference for both BCVA and CS parameters between primary pterygium and normal groups were determined via independent T-test. Results: Overall mean and standard deviation (n = 120) of BCVA and CS were found lower in primary pterygium group (0.73± 0.22LogMARand 45.00± 10.49%) compared to normal (0.12 ± 0.05 LogMAR and 6.40 ± 0.81 %) respectively. Independent T-test results showed significance difference in BCVAand CS values between primary pterygium groups and normal (both P< 0.001). Conclusions: Reduction of oculovisual function in pterygium patient is expected compared to normal. Both BCVA and CS can be used as indicator for surgical excision and prediction in early sign of reduction in visual performance.